G106(P) Targeted technical skills simulation training helps paediatric trainees with college core procedures. (12th March 2018) - Mallett, P; Watterson, C; Junk, C; Bourke, T; Thompson, A; Christie, S
Abstract : Aims: Acute Paediatrics is a stimulating and challenging training programme. The Royal College of Paediatrics and Child Health (RCPCH) provide a comprehensive curriculum for trainees during these years. In Level 1 Training (ST1–3), there are a number of core practical procedures trainees are expected to perform prior to progression to Level 2 training. These skills include Neonatal Intubation, Lumbar Puncture (LP) and Intraosseous (IO) Access. 1 Often it may be difficult for trainees to gain significant experience in these skills and achieving competence can be challenging. Reasons for this include lack of opportunity, lack of experience, and low procedural confidence. The RCPCH advocates the delivery of Simulation and Technology Enhanced Learning (TEL) including in the area of technical skills training. 2 By creating a technical skills simulation training day, we aimed to increase trainee exposure and confidence to core college procedures. Methods: We created a simulation training day for Level 1 Regional Training focused on 3 core procedures. We asked Paediatric ST1–3 trainees about previous teaching, experiences and confidence levels with these skills. Results: 24 ST1–3 trainees were surveyed. Prior to the teaching, 2 (8%) trainees felt their Intubation skills were adequate, 12 (50%) described their LP skills as satisfactory and 4 (16%) trainees labelled their IO access skills as acceptable. Following the training session, 23 of the 24 trainees (96%) felt significantly more confident in approaching all 3 of the core practical skills. All 24 Trainees (100%) felt that simulated practice helped improve their technical skills and all (100%) felt it would be useful in their daily job. Conclusion: Simulation-based training for procedural skills has been shown to be effective for trainees and has been widely used in many training programs. 3 By integrating this into the Deanery's Regional teaching programme, we have presented junior trainees the opportunity to gain vital hands-on experience on high-fidelity models, which has improved procedural exposure, enhanced user-confidence and may potentially develop procedural competence.We hope to extend this programme to higher level trainees and incorporate other core procedural skills in a bid to further promote a safe, trainee-friendly, patient-centred simulated learning environment. References: . Curriculum for Paediatric Training. General paediatrics: Level 1, 2 and 3 training August 2016. http://www.rcpch.ac.uk/training-examinations-professional-development/postgraduate-training/general-paediatrics-training/ge#curriculum . Strategy- Simulation and TEL. Royal College of Paediatrics and Child Health January 2015. http://www.rcpch.ac.uk/training-examinations-professional-development/postgraduate-training/simulation-and-technology-enh . Barsuk JH, Cohen ER, et al. Simulation-based education with mastery learning improves residents' lumbar puncture skills. Neurology2012;79(2):132–7.